Initial Assessment of the Ability of Ivermectin to Kill Ixodes scapularis and Dermacentor variabilis Ticks Feeding on Humans - Sheele, Johnathan M.; Byers, Peter A.; Sonenshine, Daniel E. (Wilderness & environmental medicine, 2013)
The purpose of this study was to determine Ixodes scapularis and Dermacentor variabilis tick mortality when fed on humans who have consumed 400 μg/kg oral ivermectin. Six study subjects, 3 in each group, were randomly assigned to receive either 400 μg/kg ivermectin or placebo in a blinded manner. After consuming either ivermectin or placebo, each study subject had 2 colostomy bags attached to his or her abdomen. One of the colostomy bags contained 7 I scapularis nymphs and 7 adults. The other colostomy bag contained 7 D variabilis nymphs and 7 adults. Tick mortality was recorded over the next 24 hours. Fifty-five percent (6 of 11) of the attached I scapularis nymphs exposed to ivermectin had morbidity (3 of 11) or died (3 of 11), compared with 0% morbidity and mortality in the 2 I scapularis nymphs that attached in the placebo group. No I scapularis adults or D variabilis nymphs attached to feed. Among D variabilis adults that attached to feed, there was a 0% mortality rate for both the placebo group (0 of 6) and the ivermectin group (0 of 8). We demonstrate a novel method to confine ticks to human subjects to study tick-borne diseases. While there was a trend toward I scapularis morbidity and mortality in the ivermectin arm, the low number of ticks that attached in the placebo group limited our analysis. Most ticks began feeding in the last 12 hours of the experiment, significantly limiting their exposure to ivermectin. Ivermectin does not cause early death in D variabilis adults.